Integrated metabolomics and proteomics reveal biomarkers associated with hemodialysis in end-stage kidney disease - Lin, Weiwei; Mousavi, Fatemeh; Blum, Benjamin C.; Heckendorf, Christian F.; Moore, Jarrod; Lampl, Noah; McComb, Mark; Kotelnikov, Sergei; Yin, Wenqing; Rabhi, Nabil; Layne, Matthew D.; Kozakov, Dima; et al. (Frontiers in Pharmacology, 2023)
We hypothesize the poor survival outcomes of end-stage kidney disease patients undergo hemodialysis are associated with low filtering efficiency and selectivity. The current gold standard criteria using single or several markers shows inability to predict or disclose the treatment effect and disease progression accurately.We performed an integrated mass spectrometry-based metabolomic and proteomic workflow capable of detecting and quantifying circulating small molecules and proteins in serum of end stage kidney disease patients. Markers linked to cardiovascular disease were validated on human iPSC-cardiomyocytes.We identified dozens of elevated molecules in serum of patients compared with healthy controls. Surprisingly, many metabolites, including lipids, remained at elevated blood concentration despite dialysis. These molecules and their associated physical interaction networks, are correlated with clinical complications in chronic kidney disease. This study confirmed two uremic toxins associated with cardiovascular disease, a major risk for patients with end-stage kidney disease.The retained molecules and metabolite-protein interaction network address a knowledge gap of candidate uremic toxins associated with clinical complications in patients undergo dialysis, providing mechanistic insights and potential drug discovery strategies for end stage kidney disease.